2014
DOI: 10.1002/ceat.201300697
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Nanogrinding of Active Pharmaceutical Ingredients

Abstract: The production of nanosuspensions via stirred‐media milling has proved to be an effective method to overcome bioavailability challenges of poorly water‐soluble active pharmaceutical ingredients (APIs). The fine‐grinding of the APIs cinnarizine and fenofibrate was investigated. Important process parameters were varied and the influence on product quality was studied. Different challenges were identified prior to and during milling: Foaming inside the milling equipment and agglomeration of fenofibrate occurred, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Using the latter, nanoparticles are generated by mechanical particle size reduction of coarse APIs. In this regard, wet media milling is the most frequently used top-down method for the production of nanosuspensions in the pharmaceutical industry [9] and has been intensively studied [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Using the latter, nanoparticles are generated by mechanical particle size reduction of coarse APIs. In this regard, wet media milling is the most frequently used top-down method for the production of nanosuspensions in the pharmaceutical industry [9] and has been intensively studied [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Stirred media milling has become an established production technique in pharmaceutical processes . Especially fine grinding to submicron particle sizes is of particular interest in order to enhance product properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the growth of naproxen during comminution could not be observed in a larger scale mill so far, the change of morphology is not solely related to the small scale of the mill used in this work. In a previous study with the API cinnarizine [38], particle growth could be identified during the comminution process using a stirred media mill and a batch size of about 400 g. This indicates that the identified ripening effect is neither specific for naproxen nor the milling equipment under investigation.…”
Section: Resultsmentioning
confidence: 94%
“…Apparently, these small fragments agglomerated during the PCS measurement, explaining both, the apparently coarse particles and the poor reproducibility of the experiment at long grinding times. According to experiences with the API cinnarizine, PCS measurements of elongated API crystals correspond rather to the width of the particles than to their length [38]. As the width of the product particles remained more or less constant from 120 to 480 min grinding, no significant differences in measured particle size could be detected via PCS.…”
Section: Resultsmentioning
confidence: 98%